High-performance ceramic composite spraying powder and preparation method thereof

The nano -carbonized silica powder is deployed and acidic, and combined with aluminum and alumina and oxide powder, adds boron silicon powder to form high -performance ceramic composite spraying powder, which solves the poor toughness of aluminum oxide -based ceramic coating coating toughness. The problem significantly improves the toughness and self -healing ability of the coating, and enhances the protection of the surface of the electrical product.

CN119349999AActive Publication Date: 2025-01-24杭州诗杭新材料科技有限公司
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411552380.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-24
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The aluminum oxide-based ceramic coating has the problem of poor toughness and is prone to impact to generate cracks or fractures, which seriously reduces the protection ability of the coated substrate.

Method used

Through sedimentation and acid treatment of nano -carbonized silicon powder, after modification, it is combined with aluminum oxide powder and oxide powder, and boronicidal powder is added to form a high -performance ceramic composite spraying powder to improve its self -healing healing Combat performance.

Benefits of technology

It significantly improves the quality and performance of ceramic composite spraying powder, enhances the toughness and self -healing ability of the coating, and improves the protection of high temperature resistance, impact resistance, corrosion resistance such as high temperature resistance, impact resistance, and corrosion of electrical products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349999A_ABST
    Figure CN119349999A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic powder, in particular to high-performance ceramic composite spraying powder and a preparation method thereof.The preparation method comprises the steps that a carbon layer is deposited on the surface of nano silicon carbide powder, acid treatment is conducted, and modified nano silicon carbide powder is obtained; preparing aluminum oxide powder and zirconium oxide powder into a suspension; adding modified nano silicon carbide powder into the suspension, and filtering, washing, drying, ball-milling and sieving the formed precipitate to obtain a composite material; the composite material and silicon boride powder are fully mixed, and the high-performance ceramic composite spraying powder is prepared. According to the preparation method, the nano silicon carbide powder is subjected to deposition treatment and acid treatment in sequence, so that the nano silicon carbide powder, the aluminum oxide powder and the zirconium oxide powder can be fully mixed, dispersed and combined, the non-uniform dispersion of the nano silicon carbide powder caused by agglomeration is prevented, and then the silicon boride powder with relatively small particle size is added; the self-healing performance of the ceramic composite spraying powder on surface cracks is improved, so that the quality of the ceramic composite spraying powder is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic powders, and in particular to a high-performance ceramic composite spray powder and a preparation method thereof. Background Art

[0002] Alumina-based ceramic powder has the advantages of high temperature resistance, corrosion resistance, and high mechanical strength. Applying it to coatings can effectively improve the high temperature resistance, oxidation resistance, and corrosion resistance of the coated substrate. However, alumina-based ceramic coatings have the problem of poor toughness and are easily cracked or broken by impact, which seriously reduces the protective ability of the coated substrate. The toughness of the ceramic coating can be improved by introducing a reinforcing phase into the ceramic matrix, such as nanofillers and nanofibers.

[0003] However, nano-scale powders have large surface energy and strong van der Waals forces, so they easily accumulate and agglomerate, and cannot be evenly dispersed in the oxide matrix. In addition, traditional nano-powders and oxide powders are often combined by mechanical strong mixing, and the bonding force between the two is weak, making it difficult to distribute them evenly, affecting the quality of the ceramic coating. Summary of the invention

[0004] In order to address the deficiencies in the prior art, the present invention provides a high-performance ceramic composite spray powder and a preparation method, wherein nano-silicon carbide is subjected to deposition treatment and acid treatment, then combined with an oxide, and then silicon boride powder is added to improve its self-healing performance for surface cracks, thereby greatly improving the quality of the ceramic composite spray powder.

[0005] To achieve the above object, the present invention provides the following technical solution: a method for preparing a high-performance ceramic composite spray powder, comprising the following steps:

[0006] (1) first depositing a carbon layer on the surface of nano-silicon carbide powder, and then subjecting it to acid treatment to obtain modified nano-silicon carbide powder;

[0007] (2) ultrasonically dispersing alumina powder and zirconium oxide powder in deionized water, and adjusting the pH to 8-9 with an alkaline solution to obtain a suspension;

[0008] (3) adding modified nano-silicon carbide powder to the suspension, slowly stirring after ultrasonic dispersion, filtering, washing, drying, ball milling, and sieving to obtain a composite material;

[0009] (4) The composite material and borosilicate powder are fully mixed and then dried to obtain a high-performance ceramic composite spray powder.

[0010] Preferably, in step (1), the surface deposition process of the nano-silicon carbide powder is: placing the nano-silicon carbide powder in a tubular furnace, using methane as a carbon source and nitrogen as a diluent gas, and using chemical vapor deposition to deposit a carbon layer on the surface of the nano-silicon carbide powder.

[0011] Preferably, the deposition temperature is controlled to be 1000-1100°C, the deposition pressure is 15-18 kPa, and the deposition time is 30-50 min. During the deposition process, the methane flow rate is controlled to be 10-15 ml / min, and the nitrogen flow rate is controlled to be 20-25 ml / min. The particle size of the nano-silicon carbide powder is 100-200 nm.

[0012] Preferably, in step (1), the acid treatment process is: pouring nano-silicon carbide with a carbon layer deposited on the surface, nitric acid solution and sulfuric acid solution into a reactor, first subjecting it to ultrasonic oscillation treatment, and then filtering and drying it.

[0013] Preferably, the volume ratio of the nitric acid solution to the sulfuric acid solution is 1:3; the mass concentration of the nitric acid solution is 60%, and the mass concentration of the sulfuric acid solution is 98%; and the ultrasonic oscillation time is 1-2h.

[0014] Preferably, in step (2), the mass ratio of alumina powder to zirconium oxide powder is 10:(1-2); and the alkaline solution is 1 mol / L sodium hydroxide solution.

[0015] Preferably, in step (3), the modified nano-silicon carbide powder accounts for 8-10% of the total mass of the alumina powder and the zirconium oxide powder.

[0016] Preferably, in step (4), the particle size of the composite material is 30-50 μm, and the particle size of the boron silicon powder is 15-20 μm.

[0017] Preferably, in step (4), silicon boride accounts for 5-10% of the total mass of the composite material.

[0018] The present invention also provides a high-performance ceramic composite spray powder prepared according to the above preparation method. The high-performance ceramic composite spray powder can be used as a green special refractory ceramic coating on the surface of electrical products, that is, a ceramic composite coating is formed by spraying on the surface of the electrical product to improve the fire resistance, high temperature resistance, impact resistance, corrosion resistance and other properties of the electrical product, and play a better protective role.

[0019] The present invention provides a high-performance ceramic composite spray powder and a preparation method, which has the following beneficial effects compared with the prior art:

[0020] The present invention sequentially performs deposition treatment and acid treatment on the nano silicon carbide powder, which can promote the full mixing and combination of the nano silicon carbide powder with the aluminum oxide powder and the zirconium oxide powder, prevent the nano silicon carbide powder from agglomerating and causing uneven dispersion, and then add silicon boride powder with a relatively small particle size to improve its self-healing performance for surface cracks, thereby greatly improving the quality of the ceramic composite spray powder.

[0021] The present invention adopts a chemical vapor deposition method to deposit a carbon layer on the surface of nano silicon carbide powder, thereby reducing the van der Waals force between nano silicon carbide, thereby weakening the agglomeration phenomenon, so that the nano silicon carbide can be evenly dispersed in an oxide matrix; at the same time, the carbon layer on the surface of the nano silicon carbide powder is treated with acid, so that it carries a negative charge under alkaline conditions, and the oxide in the suspension carries a positive charge, and the two are relatively evenly combined to form a composite material through electrostatic attraction. This strong combination effect far exceeds ordinary mechanical mixing, is conducive to the uniform dispersion of nano silicon carbide in the oxide matrix, and the two are evenly distributed, thereby improving the performance of the ceramic composite spray powder.

[0022] The present invention adds boron silicon powder to the composite material. When cracks are generated in the prepared coating, the composite material is subjected to medium-temperature oxidation treatment to generate boron silicon oxide and boron oxide. The generated boron oxide overflows into the cracks in a liquid form, expands in volume after cooling, and fills the cracks, thereby realizing self-healing of the substrate. Moreover, the boron silicon does not generate gas during oxidation, and thus does not generate pores, thereby ensuring the quality of the formed coating or ceramic material. In addition, the composite material with a large particle size and the boron silicon with a small particle size are used in combination, which has a positive effect on improving the performance of the ceramic composite spray powder. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0024] Figure 1 This is a schematic diagram of the combination and distribution of nano-silicon dioxide and oxide matrix of the present invention. DETAILED DESCRIPTION

[0025] The following examples are used to explain the implementation methods of the present application in detail, so that the implementation process of how the present application uses technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly.

[0026] Example 1

[0027] The surface deposition process of nano-SiC powder is as follows: put nano-SiC powder with a particle size of 100-200nm into a tube furnace, use methane with a flow rate of 15ml / min as the carbon source and nitrogen with a flow rate of 20ml / min as the dilution gas, and use chemical vapor deposition to deposit a carbon layer on the surface of the nano-SiC powder. During this period, the deposition temperature is controlled to be 1100℃, the deposition pressure is 15kPa, and the deposition time is 50min.

[0028] The acid treatment process of nano-silicon carbide with a carbon layer deposited on the surface is as follows: pour the nano-silicon carbide with a carbon layer deposited on the surface, 60wt% nitric acid solution and 98wt% sulfuric acid solution into a reactor, control the volume ratio of the nitric acid solution and the sulfuric acid solution to be 1:3, first treat it with ultrasonic oscillation for 1h, then filter and dry it.

[0029] Example 2

[0030] The surface deposition process of nano-SiC powder is as follows: put nano-SiC powder with a particle size of 100-200nm into a tube furnace, use methane with a flow rate of 10ml / min as the carbon source and nitrogen with a flow rate of 25ml / min as the dilution gas, and use chemical vapor deposition to deposit a carbon layer on the surface of the nano-SiC powder. During this period, the deposition temperature is controlled to be 1000℃, the deposition pressure is 18kPa, and the deposition time is 30min.

[0031] The acid treatment process of nano-silicon carbide with a carbon layer deposited on the surface is as follows: pour the nano-silicon carbide with a carbon layer deposited on the surface, 60wt% nitric acid solution and 98wt% sulfuric acid solution into a reactor, control the volume ratio of the nitric acid solution and the sulfuric acid solution to be 1:3, first treat it with ultrasonic oscillation for 2h, then filter and dry it.

[0032] Example 3

[0033] The surface deposition process of nano-SiC powder is as follows: put nano-SiC powder with a particle size of 100-200nm into a tube furnace, use methane with a flow rate of 12ml / min as the carbon source and nitrogen with a flow rate of 22ml / min as the dilution gas, and use chemical vapor deposition to deposit a carbon layer on the surface of the nano-SiC powder. During this period, the deposition temperature is controlled to be 1050℃, the deposition pressure is 16kPa, and the deposition time is 40min.

[0034] The acid treatment process of nano-silicon carbide with a carbon layer deposited on the surface is as follows: pour the nano-silicon carbide with a carbon layer deposited on the surface, 60wt% nitric acid solution and 98wt% sulfuric acid solution into a reactor, control the volume ratio of the nitric acid solution and the sulfuric acid solution to be 1:3, first treat it with ultrasonic oscillation for 1.5h, then filter and dry it.

[0035] Example 4

[0036] A method for preparing high-performance ceramic composite spray powder comprises the following steps:

[0037] (1) First, a carbon layer is deposited on the surface of the nano-silicon carbide powder (using the deposition process in Example 1), and then the powder is subjected to an acid treatment (using the acid treatment process in Example 1) to obtain a modified nano-silicon carbide powder.

[0038] (2) Alumina powder and zirconium oxide powder were ultrasonically dispersed in deionized water at a mass ratio of 10:1, and the pH was adjusted to 8 with a 1 mol / L sodium hydroxide solution to obtain a suspension.

[0039] (3) adding modified nano-silicon carbide powder to the suspension, slowly stirring after ultrasonic dispersion, filtering, washing, drying, ball-milling, and sieving to obtain a composite material; wherein the modified nano-silicon carbide powder accounts for 8% of the total mass of the alumina powder and the zirconia powder.

[0040] (4) The composite material with a particle size of 50 μm and the boronized silicon powder with a particle size of 20 μm are fully mixed, and the boronized silicon powder accounts for 5% of the total mass of the composite material, and then dried to obtain a high-performance ceramic composite spray powder.

[0041] Example 5

[0042] A method for preparing high-performance ceramic composite spray powder comprises the following steps:

[0043] (1) First, a carbon layer is deposited on the surface of the nano-silicon carbide powder (using the deposition process in Example 2), and then the powder is subjected to an acid treatment (using the acid treatment process in Example 2) to obtain a modified nano-silicon carbide powder.

[0044] (2) Alumina powder and zirconium oxide powder were ultrasonically dispersed in deionized water at a mass ratio of 10:2, and the pH was adjusted to 9 with a 1 mol / L sodium hydroxide solution to obtain a suspension.

[0045] (3) adding modified nano-silicon carbide powder to the suspension, slowly stirring after ultrasonic dispersion, filtering, washing, drying, ball-milling, and sieving to obtain a composite material; wherein the modified nano-silicon carbide powder accounts for 10% of the total mass of the alumina powder and the zirconia powder.

[0046] (4) The composite material with a particle size of 30 μm and the boron silicon powder with a particle size of 15 μm are fully mixed, and the boron silicon powder accounts for 10% of the total mass of the composite material, and then dried to obtain a high-performance ceramic composite spray powder.

[0047] Example 6

[0048] A method for preparing high-performance ceramic composite spray powder comprises the following steps:

[0049] (1) First, a carbon layer is deposited on the surface of the nano-silicon carbide powder (using the deposition process in Example 3), and then it is subjected to acid treatment (using the acid treatment process in Example 3) to obtain modified nano-silicon carbide powder.

[0050] (2) Alumina powder and zirconium oxide powder were ultrasonically dispersed in deionized water at a mass ratio of 10:1.5, and the pH was adjusted to 8.5 with 1 mol / L sodium hydroxide solution to obtain a suspension.

[0051] (3) adding modified nano-silicon carbide powder to the suspension, slowly stirring after ultrasonic dispersion, filtering, washing, drying, ball-milling, and sieving to obtain a composite material; wherein the modified nano-silicon carbide powder accounts for 9% of the total mass of the alumina powder and the zirconia powder.

[0052] (4) The composite material with a particle size of 40 μm and the boronized silicon powder with a particle size of 17 μm are fully mixed, and the boronized silicon powder accounts for 8% of the total mass of the composite material. The composite material is then dried to obtain a high-performance ceramic composite spray powder.

[0053] Example 7

[0054] It is basically the same as Example 6, except that in step (1), the deposition process and acid treatment process in Example 1 are adopted.

[0055] Example 8

[0056] It is basically the same as Example 6, except that in step (1), the deposition process and acid treatment process in Example 2 are adopted.

[0057] Comparative Example 1

[0058] A method for preparing high-performance ceramic composite spray powder comprises the following steps:

[0059] (1) Alumina powder and zirconium oxide powder were ultrasonically dispersed in deionized water at a mass ratio of 10:1.5, and the pH was adjusted to 8.5 with a 1 mol / L sodium hydroxide solution to obtain a suspension.

[0060] (2) Adding nano-silicon carbide powder to the suspension, slowly stirring after ultrasonic dispersion, filtering, washing, drying, ball-milling, and sieving to obtain a composite material; wherein the nano-silicon carbide powder accounts for 9% of the total mass of the alumina powder and the zirconia powder.

[0061] (3) The composite material with a particle size of 40 μm and the boronized silicon powder with a particle size of 17 μm are fully mixed, and the boronized silicon powder accounts for 8% of the total mass of the composite material, and then dried to obtain a high-performance ceramic composite spray powder.

[0062] Comparative Example 2

[0063] A method for preparing high-performance ceramic composite spray powder comprises the following steps:

[0064] (1) The nano-silicon carbide powder is subjected to acid treatment (using the acid treatment process in Example 3) to obtain modified nano-silicon carbide powder.

[0065] (2) Alumina powder and zirconium oxide powder were ultrasonically dispersed in deionized water at a mass ratio of 10:1.5, and the pH was adjusted to 8.5 with 1 mol / L sodium hydroxide solution to obtain a suspension.

[0066] (3) adding modified nano-silicon carbide powder to the suspension, slowly stirring after ultrasonic dispersion, filtering, washing, drying, ball-milling, and sieving to obtain a composite material; wherein the modified nano-silicon carbide powder accounts for 9% of the total mass of the alumina powder and the zirconia powder.

[0067] (4) The composite material with a particle size of 40 μm and the boronized silicon powder with a particle size of 17 μm are fully mixed, and the boronized silicon powder accounts for 8% of the total mass of the composite material. The composite material is then dried to obtain a high-performance ceramic composite spray powder.

[0068] Comparative Example 3

[0069] A method for preparing high-performance ceramic composite spray powder comprises the following steps:

[0070] (1) First, a carbon layer is deposited on the surface of nano-silicon carbide powder (using the deposition process in Example 3) to obtain modified nano-silicon carbide powder.

[0071] (2) Alumina powder and zirconium oxide powder were ultrasonically dispersed in deionized water at a mass ratio of 10:1.5, and the pH was adjusted to 8.5 with 1 mol / L sodium hydroxide solution to obtain a suspension.

[0072] (3) adding modified nano-silicon carbide powder to the suspension, slowly stirring after ultrasonic dispersion, filtering, washing, drying, ball-milling, and sieving to obtain a composite material; wherein the modified nano-silicon carbide powder accounts for 9% of the total mass of the alumina powder and the zirconia powder.

[0073] (4) The composite material with a particle size of 40 μm and the boronized silicon powder with a particle size of 17 μm are fully mixed, and the boronized silicon powder accounts for 8% of the total mass of the composite material. The composite material is then dried to obtain a high-performance ceramic composite spray powder.

[0074] Comparative Example 4

[0075] The method is basically the same as Example 6, except that the boron silicon dioxide powder with a particle size of 17 μm in step (4) is replaced with boron silicon dioxide powder with a particle size of 40 μm.

[0076] Comparative Example 5

[0077] It is basically the same as Example 6, except that in step (2), only alumina powder is used.

[0078] Comparative Example 6

[0079] The method is basically the same as Example 6, except that in step (4), no borosilicate powder is added, that is, the composite material prepared in step (3) is regarded as a high-performance ceramic composite spray powder.

[0080] Quality Inspection

[0081] 1. With metal as substrate, the ceramic composite spray powders in Examples 4-8 and Comparative Examples 1-6 were sprayed on the metal surface by plasma spraying, and the coating thickness was controlled to be about 400 μm. The microhardness of the coating was tested by a microhardness tester; the bonding strength of the coating was tested by a scratch method. The fracture toughness of the coating was tested by an indentation method. The specific results are shown in the following table.

[0082] Table 1 Coating properties

[0083] category Microhardness(HV) Bonding strength (MPa) <![CDATA[Fracture toughness (MPa·m 1 / 2 )]]> Example 4 1490 151.3 9.8 Example 5 1498 152.7 10.2 Example 6 1521 158.8 10.5 Example 7 1510 155.2 10.2 Example 8 1513 155.7 10.3 Comparative Example 1 1205 127.4 6.6 Comparative Example 2 1314 138.9 7.7 Comparative Example 3 1243 131.2 6.9 Comparative Example 4 1509 147.1 9.4 Comparative Example 5 1417 156.4 9.6 Comparative Example 6 1505 150.6 8.9

[0084] 2. The high-performance ceramic composite spray powders in Example 6, Comparative Example 4 and Comparative Example 6 were pressed and sintered to obtain a sample bar of size 3×4×20 mm, and its bending strength was tested, which was the original bending strength. The loading load and holding time were set to 98N / 15s, cracks were made on the sample bar, and its bending strength was tested, which was the damaged bending strength. The cracked sample bar was kept at 700°C for 30 minutes, and its bending strength was tested, which was the restored bending strength. Healing rate = restored bending strength / original bending strength × 100%. The specific results are shown in the following table.

[0085] Table 2 Self-healing

[0086]

[0087] It can be seen from the above table that the coating prepared by using the high-performance ceramic composite spray powder in the embodiment has excellent surface hardness, bonding strength and fracture toughness; and the added small-particle silicon boride powder can significantly improve the self-healing performance of the ceramic composite spray powder.

[0088] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing high-performance ceramic composite spray powder, characterized in that: The following steps are involved: (1) first depositing a carbon layer on the surface of nano-silicon carbide powder, and then subjecting it to acid treatment to obtain modified nano-silicon carbide powder; (2) ultrasonically dispersing alumina powder and zirconium oxide powder in deionized water, and adjusting the pH to 8-9 with an alkaline solution to obtain a suspension; (3) adding modified nano-silicon carbide powder to the suspension, slowly stirring after ultrasonic dispersion, filtering, washing, drying, ball milling, and sieving to obtain a composite material; (4) The composite material and borosilicate powder are fully mixed and then dried to obtain a high-performance ceramic composite spray powder.

2. The method for preparing a high-performance ceramic composite spray powder according to claim 1, characterized in that: In step (1), the surface deposition process of nano-silicon carbide powder is as follows: the nano-silicon carbide powder is placed in a tubular furnace, methane is used as a carbon source, nitrogen is used as a diluent gas, and a carbon layer is deposited on the surface of the nano-silicon carbide powder by chemical vapor deposition.

3. The method for preparing a high-performance ceramic composite spray powder according to claim 2, characterized in that: The deposition temperature is controlled to be 1000-1100°C, the deposition pressure is controlled to be 15-18kPa, and the deposition time is controlled to be 30-50min. During the deposition process, the methane flow rate is controlled to be 10-15ml / min, and the nitrogen flow rate is controlled to be 20-25ml / min. The particle size of the nano-silicon carbide powder is 100-200nm.

4. The method for preparing a high-performance ceramic composite spray powder according to claim 1, characterized in that: In step (1), the acid treatment process is: pouring the nano-silicon carbide with a carbon layer deposited on the surface, nitric acid solution and sulfuric acid solution into a reactor, first subjecting it to ultrasonic oscillation treatment, and then filtering and drying it.

5. The method for preparing a high-performance ceramic composite spray powder according to claim 4, characterized in that: The volume ratio of the nitric acid solution to the sulfuric acid solution is 1:3; the mass concentration of the nitric acid solution is 60%, and the mass concentration of the sulfuric acid solution is 98%; and the ultrasonic oscillation time is 1-2h.

6. The method for preparing a high-performance ceramic composite spray powder according to claim 1, characterized in that: In step (2), the mass ratio of alumina powder to zirconium oxide powder is 10:(1-2); and the alkaline solution is 1 mol / L sodium hydroxide solution.

7. The method for preparing a high-performance ceramic composite spray powder according to claim 1, characterized in that: In step (3), the modified nano silicon carbide powder accounts for 8-10% of the total mass of the alumina powder and the zirconium oxide powder.

8. The method for preparing a high-performance ceramic composite spray powder according to claim 1, characterized in that: In step (4), the particle size of the composite material is 30-50 μm, and the particle size of the boron silicon powder is 15-20 μm.

9. The method for preparing a high-performance ceramic composite spray powder according to claim 1, characterized in that: In step (4), silicon boride accounts for 5-10% of the total mass of the composite material.

10. A high performance ceramic composite spray powder prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • ZrB2 / SiC composite powder special for thermal spraying ceramic coating and preparation method of ZrB2 / SiC composite powder

    CN106316402A

  • Graphene coated alumina ceramic powder as well as preparation method and application thereof

    CN107353017A

  • Functional ceramic body as well as preparation method and application thereof

    CN110526739A

  • Preparation method of silicon carbide ceramic-based composite material with self-repairing function

    CN113943160A

  • Ceramic cutter material modified based on core-shell type nano composite powder and preparation method of ceramic cutter material

    CN114988887A